A view from the roof: Magmatic stoping in the shallow crust, Chita pluton, Argentina - Yoshinobu, Aaron S. (2003)
Nearly 2 km of vertical relief and exposure of continuous pluton roof-wall corners around the Chita pluton, northwest Argentina, provides constraints on the 3-D host rock displacement field attending magma emplacement in the shallow crust. The pluton is rectangular in cross-sectional view and consists of weakly to non-deformed granite to granodiorite. Structures in surrounding metasedimentary host rocks are truncated at a knife-sharp contact and are only weakly deflected from their regional orientations. Final emplacement occurred by stoping together with minor doming of the earth's surface. Structural restoration of a cross-section indicates that host-rocks above the pluton may have been domed upwards during emplacement by as much as a few hundred meters, accounting for up to 20% of the exposed pluton volume. The remaining 80% of the space for pluton emplacement was made by downward removal of host-rock from the present level of exposure. Although mechanisms such as floor-subsidence are permissive, late stoping has destroyed evidence for the early emplacement history. However, geometrical constraints provided by exposure of continuous wall-to-roof contacts indicate that early emplacement mechanisms at this level in the crust and immediately below were also dominated by the downward displacement of host rocks through a conduit that now is represented by the solidified pluton. © 2002 Elsevier Science Ltd.